2016
DOI: 10.5539/ells.v6n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Saudi EFL Readers Exhibit Poor Reading Abilities?

Abstract: The aim of the current study was to investigate the reasons behind Saudi learners' poor reading skills. To this end, the objectives were to identify the reading habits of Saudi English as a Foreign Language (EFL) middle school learners, to understand the extent to which Saudi EFL middle school learners use reading comprehension skills and to explore the perceptions of learners, teachers and supervisors regarding Saudi EFL learners' reading abilities. The study sample consisted of 90 Saudi EFL middle school stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…Most of Saudi students lack the necessary reading habits (Al-Qahtani, 2016), and they have difficulties in different areas such as use of vocabulary, scanning, skimming, prediction and summarizing (Nezami, 2012). They rarely make use of important reading skills when they read English texts as a result of lack of exposure to the target language, poor teaching skills, little attention to comprehension, lack of motivation, unfamiliar and unsuitable reading topics, lack of reading skills training and limited vocabulary (Al-Qahtani, 2016).…”
Section: Language Skills Of Saudi Efl Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of Saudi students lack the necessary reading habits (Al-Qahtani, 2016), and they have difficulties in different areas such as use of vocabulary, scanning, skimming, prediction and summarizing (Nezami, 2012). They rarely make use of important reading skills when they read English texts as a result of lack of exposure to the target language, poor teaching skills, little attention to comprehension, lack of motivation, unfamiliar and unsuitable reading topics, lack of reading skills training and limited vocabulary (Al-Qahtani, 2016).…”
Section: Language Skills Of Saudi Efl Studentsmentioning
confidence: 99%
“…Most of Saudi students lack the necessary reading habits (Al-Qahtani, 2016), and they have difficulties in different areas such as use of vocabulary, scanning, skimming, prediction and summarizing (Nezami, 2012). They rarely make use of important reading skills when they read English texts as a result of lack of exposure to the target language, poor teaching skills, little attention to comprehension, lack of motivation, unfamiliar and unsuitable reading topics, lack of reading skills training and limited vocabulary (Al-Qahtani, 2016). Regarding oral proficienc , it has been found that Saudi students have difficulties in pronouncing certain English consonant sounds (Ahmad, 2011;Hago & Khan, 2015).Pronunciation, speed of speech, insufficient vocabulary, the different accent of speakers, lack of concentration, anxiety, bad quality of recording, appropriate grammatical structures, hesitance to use the target language, conceptual knowledge, listening ability, motivation to speak, teachers' feedback during speaking activities, confidence, mother tongue, low participation time allow to speak and time allowed for preparation were the major listening comprehension problems encountered by Saudi EFL learners (AlAsmari, 2015;Hamouda, 2013a;Younes & Albalawi, 2016).…”
Section: Language Skills Of Saudi Efl Studentsmentioning
confidence: 99%
“…Some studies have reported that Saudi EFL students hardly read in English (e.g. Al-Homoud, 2003;Al-Qahtani, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…This huge indeterminate response requires to be addressed it may be because of their less understanding of the textbook contents resulting from their inappropriate level of English language proficiency. Studies prove that the Saudi tertiary level English students' English proficiency is not up to the expectations (Moskovsky & Alrabai, 2009;Al-Zubeiry, 2012;Al-Qahtani, 2016). Further studies are imperative to know about the indeterminate state of the learners.…”
Section: Findings and Discussionmentioning
confidence: 99%